Analyzing the Challenges and Opportunities of History Learning in the Era of Society 5.0 - Afwan, Bahtiar; Setiawan, Johan; Hartati, Umi; Suryani, Susi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The text provided seems to discuss the transformation of history education in the Society 5.0 era, a concept where advanced technologies like the Internet of Things (IoT), artificial intelligence (AI), and big data are integrated into everyday life. The main points include opportunities and challenges in history education, such as access to digital resources and the digital divide. It emphasizes the need to develop students' critical and analytical thinking skills and adapt teaching models to the characteristics of Generation Z, who are more digital and independent. The study uses a descriptive qualitative approach and case studies to explore how technology can effectively enhance history education, making learning more meaningful and inclusive. It concludes that an adaptive and personalized approach, along with continuous teacher training, is crucial to address challenges and maximize opportunities in history education in the Society 5.0 era.